2015
DOI: 10.3390/resources4030621
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Device to Convert Olive Mill Wastewater into a Suitable Effluent for Feeding Purple Non-Sulfur Photosynthetic Bacteria

Abstract: A device (prototype) with a working volume of 200 L was used to deplete olive mill wastewater (OMW) of polyphenols. The OMW transformed into feedstock by means of the device was then used for feeding a lab-scale photobioreactor, just for testing the production of bioH2. The main novelty of this prototype consists in the combination of several adsorbent matrices and the exploitation of their synergic action. In this investigation, three matrices have been used: active carbon, Azolla and zeolite. The device was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Moreover, the cultivation and harvesting practices had a large influence on the microbial community distribution in OMWS. For example, Carlozzi et al (2015) showed that fermentative bacteria in OMWS resulting from the early collection and harvesting “hand collection” of the Olea europaea variety were restricted to the two families Peptococcaceae and Sporolactobacillaceae ( Kavroulakis and Ntougias, 2011 ). On another note, the very few studies that thoroughly investigated the fungal diversity in OMWS reported very contrasting results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the cultivation and harvesting practices had a large influence on the microbial community distribution in OMWS. For example, Carlozzi et al (2015) showed that fermentative bacteria in OMWS resulting from the early collection and harvesting “hand collection” of the Olea europaea variety were restricted to the two families Peptococcaceae and Sporolactobacillaceae ( Kavroulakis and Ntougias, 2011 ). On another note, the very few studies that thoroughly investigated the fungal diversity in OMWS reported very contrasting results.…”
Section: Discussionmentioning
confidence: 99%